Identities arising from binomial-like formulas involving divisors of numbers - Gryszka, Karol (Annales Mathematicae Silesianae, 2023)
In this article, we derive a great number of identities involving the ω function counting distinct prime divisors of a given number n. These identities also include Pochhammer symbols, Fibonacci and Lucas numbers and many more.